Design of a Web-Based Logistics Management Information System Using PIECES Analysis at PT Cahaya Lautmas Djaya - Hijrah Putri; Muhammad Ridho Ardiansyah (Journal Innovation in Information and Computer Technology, 2026)
PT Cahaya Lautmas Djaya still manages several logistics activities through a semi-manual and fragmented workflow, including WhatsApp groups, Google Forms, Microsoft Excel, and physical documents. This condition causes operational problems such as slow request order approval, stock discrepancies, document mismatch, delayed material return handling, weak data control, and the risk of local data loss. This study aims to design a web-based logistics management information system using PIECES analysis to support more integrated logistics operations between the Palembang head office and the Sungai Baung site. This study used a descriptive system design approach. Data were collected through observation, interviews, and documentation of the current logistics process. The current system was analyzed using the PIECES framework, covering Performance, Information, Economics, Control, Efficiency, and Service aspects. The proposed system was modeled using Data Flow Diagram and Entity Relationship Diagram to describe data flow and database structure. The results show that the proposed system integrates digital request order, real-time approval, purchasing, QR Code-based delivery note, material tracking, automatic inventory update, return handling, access control, and cloud-based backup. The DFD design describes the flow of logistics data among users, processes, and data storage, while the ERD design supports structured relationships among users, materials, request orders, delivery notes, stock records, tracking data, and return transactions. The proposed system is expected to improve data accuracy, operational efficiency, document control, warehouse monitoring, and coordination between the head office and the site. This study is limited to the analysis and design stage; therefore, further research is recommended to continue with system implementation, black-box testing, user acceptance testing, and performance evaluation.